The 3D characterization of corrosion in aluminium alloys - Chew, Boon How (2014)
Corrosion is an ongoing problem till date. Lots of attention has been given to it as it has already cost governments millions of dollars in damage and also many human lives. Structural integrity is deeply affected when the structures undergo cyclic loading. This results in fatigue failure as corrosion may act as defects and cause propagation of cracks periodically. This paper focuses on characterizing pitting corrosion three dimensionally on two materials, aluminium alloy 7075 and 2524 that are mainly used in aircraft structures due to their high strength to weight ratio. Volumetric analysis and stress analysis are used to characterize pit shapes. Three shapes, truncated sphere, half ellipsoid and elliptical cone, were analyzed in volumetric analysis using several software like ImageJ, MATLAB, and Microsoft Excel. It was found that elliptical cone provides the best estimate in terms of volume. However, elliptical cone was not used in the subsequent stress analysis as the tip of the cone acts as a major stress concentrator which will incur huge stress. In the finite element analysis, truncated sphere and half ellipsoid were used as ideal pits in comparison to the actual pits. It was found that both shapes provided relatively close results to the actual pits, with half ellipsoid providing a closer estimate in comparing the corrosion time of 240 hours. From this report, it can be concluded that AA7075 is less corrosion resistant than AA2524, and corrosion on AA7075 will cause a worse impact on the structure integrity due to higher stress concentration factor found in the pits compared to AA2524